가스분무법으로 제조된 Al 합금분말의 펄스통전 소결체의 특성평가 - 박현국; Hyun-kuk Park; 장준호; Jun-ho Jang; 이정한; Jung-han Lee; 오익현; Ik-hyun Oh (대한금속·재료학회지, 55(10), 2017)
In this study, Al alloy targets were fabricated using the powder metallurgy (pulsed current activated sintering, PCAS) process for metal PVD coating target applications. Powders were prepared from Al, Si and Cu ingots for sintering Al alloy compacts using the gas atomizing process. To fabricate the gas atomized Al alloy powders, processing conditions, such as melting temperature, processing time and gas pressure were optimized and controlled during the gas atomizing process. Al alloy compacts with 200 mm diameters and 1/4 inch thickness were fabricated using a 30,000 A pulsed current activated sintering machine. During the Al alloy compact sintering process, sintering conditions such as temperature, pulse ratio, pressure, and heating rate were controlled and optimized. The Al alloy compacts were fabricated under a uniaxial pressure of 60 MPa at a sintering temperature of 400 ℃ without any significant change in grain size. The grain size and relative density of the Al alloy compacts were 7.3 ㎛ and 100%, respectively. The properties of thin films deposited on a Si substrate using the PCASed target materials were compared with those from a commercial target material prepared using the casting melting process. The thicknesses of the thin films deposited on the Si substrate using the PCASed target material and a commercial target material were about 494 nm and 450 nm, respectively. The specific resistance and surface roughness of the PCASed thin film and commercial thin film were 4.012 × 10 -6 and 4.012 × 10 -6 , 6.105 nm and 6.928 nm, respectively. (Received June 16, 2017; Accepted July 4, 2017)